Peran Manajemen Sumber Daya Manusia dalam Kegiatan GEMARI (Gerakan Masyarakat Mengumpulkan Sampah Plastik) di Tlogosari Wetan, Semarang - Khairi, Imam Abul; Nurhidayati, Roro (Maddah: Journal of Advanced Da'wah Management Research, 2024)
The issue of plastic waste management has become an urgent global environmental concern, including in Indonesia, the second-largest producer of plastic waste worldwide. Tlogosari Wetan, Semarang, faces a similar crisis with a high volume of plastic waste polluting the environment. GEMARI (Gerakan Masyarakat Mengumpulkan Sampah Plastik) is a local initiative aimed at reducing plastic waste through community participation. However, previous literature has primarily focused on technical and infrastructural aspects of waste management. This research addresses the gap in understanding the role of human resource management (HRM) in enhancing the effectiveness of community participation, providing new insights into community-based management. This study aims to understand the role of human resource management in the GEMARI program in Tlogosari Wetan, Semarang. Using a qualitative research method, data was collected through interviews, observation, and documentation. The results reveal that: 1) Workforce planning involves human resource management through collaboration between healthcare workers, community leaders, and residents engaged in waste collection; 2) Strategic planning, including active community participation in health and waste management programs, improves environmental cleanliness and access to free healthcare services; and 3) Recruitment is informal, driven by strong community awareness, supported by local government efforts that ensure program consistency and sustainability through ongoing socialization efforts.